Correlation Between “PATUH” Program and Blood Pressure Values in Elderly Hypertensive Patients in Posyandu in Ledug Village - Andika, Anggun; Riyaningrum, Wahyu (UM Purwokerto Press, 2025)
Blood pressure is a primary cause of death among hypertensive patients. Physiologically, advancing age increases the risk of hypertension. Factors contributing to hypertension include unhealthy lifestyle patterns. The PATUH program is a beneficial initiative for hypertensive patients in managing blood pressure. PATUH stands for regular health check-ups and following doctor's recommendations, managing diseases with appropriate and regular medication, maintaining a balanced diet and nutrition, engaging in safe physical activities, and avoiding cigarette smoke, alcohol, and other carcinogenic substances. The research design employed was descriptive retrospective with a cross-sectional approach. The study population consisted of 93 elderly hypertensive patients in Posyandu (Elderly Integrated Health Post) in Ledug Village. The sample included 38 elderly individuals who met the inclusion and exclusion criteria. Based on PATUH behavior, 35 elderly individuals (92.1%) were classified as adherent, 2 (5.3%) as moderately adherent, and 1 (2.6%) as non-adherent. In terms of average blood pressure results, 19 individuals (50%) were classified as pre-hypertensive, 18 (47.4%) as stage 1 hypertensive, and 1 (2.6%) as stage 2 hypertensive. There is a significant correlation between the PATUH program and blood pressure values in elderly hypertensive patients in Posyandu in Ledug Village, with a P value (p=0.000**) and a correlation coefficient of 0.76, indicating a highly significant and strong correlation.